Universal Dynamics of Molecular Reorientation in Hybrid Lead Iodide Perovskites - Fabini, Douglas H; Siaw, Ting Ann; Stoumpos, Constantinos C; Laurita, Geneva; Olds, Daniel; Page, Katharine; Hu, Jerry G; Kanatzidis, Mercouri G; Han, Songi; Seshadri, Ram (Journal of the American Chemical Society, 2017)
The role of organic molecular cations in the high-performance perovskite photovoltaic absorbers, methylammonium lead iodide (MAPbI3) and formamidinium lead iodide (FAPbI3), has been an enigmatic subject of great interest. Beyond aiding in the ease of processing of thin films for photovoltaic devices, there have been suggestions that many of the remarkable properties of the halide perovskites can be attributed to the dipolar nature and the dynamic behavior of these cations. Here, we establish the dynamics of the molecular cations in FAPbI3 between 4 K and 340 K and the nature of their interaction with the surrounding inorganic cage using a combination of solid state nuclear magnetic resonance and dielectric spectroscopies, neutron scattering, calorimetry, and ab initio calculations. Detailed comparisons with the reported temperature dependence of the dynamics of MAPbI3 are then carried out which reveal the molecular ions in the two different compounds to exhibit very similar rotation rates (≈8 ps) at room temperature, despite differences in other temperature regimes. For FA, rotation about the N···N axis, which reorients the molecular dipole, is the dominant motion in all phases, with an activation barrier of ≈21 meV in the ambient phase, compared to ≈110 meV for the analogous dipole reorientation of MA. Geometrical frustration of the molecule–cage interaction in FAPbI3 produces a disordered γ-phase and subsequent glassy freezing at yet lower temperatures. Hydrogen bonds suggested by atom–atom distances from neutron total scattering experiments imply a substantial role for the molecules in directing structure and dictating properties. The temperature dependence of reorientation of the dipolar molecular cations systematically described here can clarify various hypotheses including those of large-polaron charge transport and fugitive electron spin polarization that have been invoked in the context of these unusual materials.